Growth and Distribution of Population in Basti City (1901-2011) - Mishra, Katyayni; Singh, Arun K. (National Geographical Journal of India, 2022)
Population is the basic resource and its impact on overall development becomes the key factor in the local level planning. Population characteristics and socio-economic factors determine the direction and destiny of urban development. The socio-economic conditions are very much influenced and governed by the different demographic characteristics like growth of population, their distribution and density pattern, sex composition, literacy etc. These demographic characteristics are conditioned by the attractive and restrictive factors like physico-cultural, infrastructural development like urban water supply and sewerage facilities and transportation etc. This paper intends to examine the aspects of population of a class I city i.e. Basti in spatio- temporal context.